PENGUJIAN QUALITY OF SERVICE (Qos) LAYANAN VIDEO STREAMING PADA JARINGAN WIRELESS MENGGUNAKAN METODE HTB (HIERARCHICAL TOKEN BUCKET) (STUDI KASUS PADA UPT TIK UNIVERSITAS PAPUA KABUPATEN MANOKWARI): PENGUJIAN QUALITY OF SERVICE (Qos) LAYANAN VIDEO STREAMING PADA JARINGAN WIRELESS MENGGUNAKAN METODE HTB (HIERARCHICAL TOKEN BUCKET) (STUDI KASUS PADA UPT TIK UNIVERSITAS PAPUA KABUPATEN MANOKWARI) - novalin kladit; Fridolin F. paiki; Christian Dwi Suhendra (Universitas Papua, 2024)
At the same time as the increase in internet users in Indonesia, the number of users has also increased for both video and audio streaming. This increase is based on very rapid technological developments, especially notebooks and tablets that use wireless internet access. The use of streaming video transmission over a wireless network is different from a cable network because the characteristics of wireless networks are limited compared to cable networks, and the characteristics of streaming video transmission require different handling from text data transmission in general. To maintain the stability of internet services for users who access various applications on the internet, the QOS (Quality Of Service) method will be implemented on wireless networks with HTB (Hierarchical Token Bucket) data used, namely video with quality 240p, 360p, 480p, 720p. The QoS parameters analyzed consist of Delay, Jitter, Packet Loss, and Throughput. Test results using the RTP protocol for video streaming have a jitter value of 0 ms because RTP is designed to compensate for jitter and desequencing, if a packet is dropped or lost in the network then RTP will not retransmit to avoid delays due to retransmission requests. To get good video results, packet loss must be between 0% - 3%. If the packet loss is more than 3%, the video results obtained are not satisfactory because the video has a lot of image and sound damage. The author conducted research at UPT Tik Unipa.